Size-dependency of concrete-filled steel tubes subject to impact loading - Mirmomeni, Mahsa; Heidarpour, Amin; Zhao, Xiao-Ling; Al-Mahaidi, Riadh; Packer, Jeffrey A. (International journal of impact engineering, 2017)
•Effect of size on the impact response of CFST sub-samples is investigated.•Different height-to-diameter and diameter-to-tube-wall thickness ratios are tested.•The dynamic increase factor (DIF) of CFSTs is proven to be size-dependent.•Interaction between concrete and steel cannot be neglected at impact rates.•New size- and rate-dependent expressions are proposed for the DIFy of CFSTs. With the increasing trend towards using concrete-filled steel tubes (CFST) in civil structures, understanding their mechanical properties under impact loads has attracted the interest of researchers. The dynamic properties of concrete confined by steel tubes are size-dependent. An experimental program was carried out to investigate the relation between the size and impact response of CFST sub-samples. High-strain-rate tests were conducted on specimens made from self-consolidating normal concrete confined by mild steel tubes. To take into account the stress uniformity and confinement effects in the specimens, various height-to-diameter ratios (H/D) and diameter-to-tube-wall thickness ratios (D/t) were considered. Dynamic increase factors (DIFs) were derived as the ratio of the material strength at high strain rate to those of the same size under quasi-static loading conditions. The results were compared to two sets of reference tests, namely unconfined concrete and hollow steel tube specimens of the same size and with the same boundary conditions. The results indicate the influence of H/D ratio, D/t ratio, and end-friction coefficient on the stress–strain distribution, dynamic compressive properties and failure modes of sub-scale concrete-filled steel tubes under impact load. The size-dependent behaviour of the CFST is found to be a function of the level of confinement the circumferential steel tube imposes on the concrete filling. Two expressions are proposed for predicting the DIF of yield stress for CFSTs: one considering the concrete–steel interaction relationship presented in Eurocode 4, and an empirical expression based on the Cowper–Symonds model for steel. The proposed rate- and size-dependent expressions show close correlations with experimental results.